Myanmar Agricultural Performance Survey (MAPS) Monsoon Season 2024: Agricultural input markets, credit and extension services - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
This note provides an overview of agricultural input access and utilization for the monsoon season 2023 based on a nationally and regionally representative sample of 4,663 crop farmers undertaken in January 22 to March 7, 2024. Key Findings  Fertilizer use rates and profitability for rice production reached their highest levels since before the coup during the 2023 monsoon season, driven primarily by higher paddy prices. Application rates for monsoon season paddy increased to 66 kg/acre from 54 kg/acre in the previous monsoon. Urea application increased from 33 kg/acre to 38 kg/acre, and non-urea fertilizers (mainly compound 15-15-15) increased from 21 kg/acre to 28 kg/acre.  The benefit-cost ratio of urea application to paddy crops averaged 2.3 at the urea sales price reported by agri-input dealers and 2.0 at farmer reported urea prices. These ratios imply a return on investment in urea fertilizer for the farmer of 130 percent at input dealer prices and 100 percent at average famer-reported prices. The difference in reported prices likely reflects interest charges and local transport costs from the dealer to the farm.  Access to mechanization services, tractors and combine harvesters was similar in monsoon 2023 compared to a year earlier, but costs increased dramatically. Plowing with a four-wheel tractor, for example, increased by 42 percent to 60,000 MMK/acre. The cost of combine harvesting averaged 110,000 MMK/acre. Timeliness of access was likely reduced as fuel shortages increased, especially in conflict areas.  The share of farmers using saved paddy seed increased from 56 percent to 61 percent nationally for use in the 2023 monsoon season compared to a year before. There were important differences across states and regions. The share of farmers purchasing seed in conflict areas fell more than the national average; by 11 percentage points in Mandalay, 7 percentage points in Rakhine, 6 percentage points in Tanintharyi, and 5 percentage points in Mon State.  Eighty-four percent of farms hired labor in the 2023 monsoon season, slightly higher than the previous monsoon season. Male wages rose to 8,800 MMK/day in the 2023 monsoon season from almost 7,400 MMK/day in the previous monsoon, an increase of 19 percent.  Despite large nominal increases, real wages for men and women nevertheless fell as the cost of a typical daily diet which rose 37 percent over the period February 2023 to March 2024.  Access to internet or mobile phone services increased by 3 percentage points from 15 percent to 18 percent, and access to private sector services increased by almost 3 percentage points from 18.0 percent to 20.6 percent. Increases in private extension access favored producers of cash crops, notably betel leaves, cotton, rice and maize. Internet or mobile phone services were sought out by producers of cotton, rice, betel leaves and pulses, again primarily cash crops.